Optimalisasi Pembelajaran Bahasa Arab Di Era Adaptasi Kebiasaan Baru (AKB) - Syindi Oktaviani Tolinggi (Taqdir, 2020)
Learning Arabic has extraordinary challenges especially now the world is facing the Corona virus pandemic (Covid-19). All learning including Arabic, turns into learning from home or online. At first, this policy was greeted with great joy by educators and students. However, in reality this policy causes confusion and challenges how to keep learning running optimally. This research uses library research method by collecting various data sources from journal articles, seminars, and various other sources relevant to the research topic. Data collection by searching, exploring, assessing data sources, and studying the existing problems, then processed with descriptive content analysis techniques. This study aims to provide an overview of how to optimize Arabic language learning in the New Habit Adaptation (AKB) era by making various adjustments to the learning components. The results of this study are a new strategy design and redesign of several learning components, are adjustment of curriculum, adjustment of learning material, adjustment of learning models and methods, adjustment of learning media, adjustment of the role of the three center curriculum, and adjustment of the assessment or evaluation of learning outcomes for language learning. So, Arabic in the era of New Habit Adaptation (AKB) can run optimally.